Keefektifan Petugas Cinta Sholat Untuk Menanamkan Kedisiplinan Dan Kekhusyukan Sholat Pada Siswa Kelas Atas Di SDIT Az-Zahra Sragen - Agustin, Isnia; , Drs. Suwarno, S.H., M.Pd (2017)
This study aims to: 1) Describe the character of discipline prayer in class in SDIT Az-Zahra Sragen. 2) Describe the absorption of prayer in the upper grade students in SDIT Az-Zahra Sragen. 3) Describe the effectiveness of Pray Love Officers to instill discipline character and solemnity of prayer on upper grade students in SDIT Az-Zahra Sragen. The research is a qualitative research with qualitative descriptive design. The informants are the principal, counselor, and students. Data collection techniques used were observation, interviews, and documentation.The data analysis techniques includes data reduction, data presentation, verification and inference. The validity of research data using a triangulation of sources and methods. The results showed that 1) Discipline prayer on upper grade students in SDIT Az-Zahra Sragen, students already pray on time, working on the terms and the pillars of prayer, prayer with the congregation, as well as the prayer has become a mandatory requirement which is usually done by the students. 2) Solemnity of prayer conducted on students upper grade SDIT Az-Zahra Sragen, it is appropriate that begins with implementing ablution, body language such as bowing and prostration piously, do not laugh, do not turn right, left, and upward, and not talk, and dhikr and pray together. 3) Pray Love Officers effectiveness in improving student discipline and prayer solemnity on upper grade students in SDIT Az-Zahra Sragen showed that activities are in accordance with its function as an exemplary Muslim builders. In his duties Pray Love Officer is in conformity with the goal of instilling character and solemnity of prayer discipline in students.